1978
DOI: 10.1056/nejm197810262991701
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of High-Density Lipoprotein Apolipoproteins in Tangier Disease

Abstract: To define the metabolic defect in Tangier disease, we studied the kinetics of [125I]-high-density lipoprotein apolipoproteins (apolipoproteins A-I and A-II) in 11 normal subjects, two obligate heterozygotes, and two homozygotes. Mean synthesis of apolipoproteins A-1 and A-11 was 8.24 mg per kilogram per day in the normal group, 7.94 in heterozygotes and 3.66 in homozygotes. The mean plasma-residence time for both apolipoproteins was 5.21 days in the normal subjects, 3.41 days in heterozygotes, and 0.52 days in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
2

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(87 citation statements)
references
References 24 publications
6
78
1
2
Order By: Relevance
“…136 In addition, it was reported 129 ' 130 that a large fraction of apo A-l in Tangier plasma was found in the 1.21 g/ml infranate. Other studies confirmed this finding, but also reported 131 that 28% of apo A-l and 9 1 % of apo A-ll in the plasma of homozygotes was found in the 1.063 g/ml supemate. Radioiodinated HDL, apo A-l, and apo A-II kinetic studies performed in homozygotes studied under steady state conditions 131 ' 134 revealed apo A-l and apo A-ll residence times of 5% and 18% of normal.…”
Section: Tangier Diseasementioning
confidence: 52%
“…136 In addition, it was reported 129 ' 130 that a large fraction of apo A-l in Tangier plasma was found in the 1.21 g/ml infranate. Other studies confirmed this finding, but also reported 131 that 28% of apo A-l and 9 1 % of apo A-ll in the plasma of homozygotes was found in the 1.063 g/ml supemate. Radioiodinated HDL, apo A-l, and apo A-II kinetic studies performed in homozygotes studied under steady state conditions 131 ' 134 revealed apo A-l and apo A-ll residence times of 5% and 18% of normal.…”
Section: Tangier Diseasementioning
confidence: 52%
“…The decreased apoE levels in plasma and brain that we observed are similar to those seen by others. 2 The decreased apoE levels in the CNS are not related to Apoe gene expression but likely result from increased catabolism of abnormally lipidated apoE-containing HDL lipoproteins produced in the CNS, as occurs with abnormally lipidated apoA-I and apoA-II that are secreted by the liver and are rapidly catabolized in the plasma of Tangier's disease patients (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, loss-of-function mutations in ABCA1 cause Tangier's disease (6 -9), which is characterized by accumulation of cholesterol in lymphatic tissues and increased catabolism of abnormally lipidated HDL, resulting in very low levels of plasma HDL and HDL-associated apolipoproteins A-I (apoA-I) and A-II (apoA-II) (10,11). ABCA1 knock-out mice (Abca1 Ϫ/Ϫ ) have been produced, and the mice have a similar phenotype as patients with Tangier's disease (12).…”
mentioning
confidence: 99%
“…Increased catabolism of LpAI and LpAI:AII leading to low HDL cholesterol concentrations is characteristic of Tangier disease and LCAT deficiency. Genetic deficiency of the ABCA1 transporter (Tangier disease) is associated with decreased cholesterol efflux and poor lipidation of pre-␤ HDL, resulting in accelerated LpAI catabolism and increased CVD (124 ). In contrast, in LCAT deficiency there is effective cholesterol efflux from cholesterolloaded macrophages followed by defective maturation of pre-␤ HDL to ␣ HDL; accelerated catabolism, primarily of LpAI:AII as well as LpAI; and renal disease, but no increased risk of CVD (125,126 ).…”
Section: Apo Ai and Apo Ai:aii Particlesmentioning
confidence: 99%